2012
DOI: 10.18705/1607-419x-2012-18-5-421-428
|View full text |Cite
|
Sign up to set email alerts
|

Apo E gene polymorphism in patients with metabolic syndrome and cognitive disorders

Abstract: Objective. Тс determine allelic variants frequencies caused by Apo E polymorphism in patients with metabolic syndrome and cognitive dysfunction (CD). Design and methods. 54 participants had undergone anthropometric measurements, blood examination (glucose, cholesterol and triglycerides), molecular genetic analysis (polymerase chain reaction, restriction fragments length polymorphism) and neuropsychological tests. Results. Allelic variant s4 of Apo E is an unfavourable factor contributing to the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
2
1
0
Order By: Relevance
“…The ε3 allele was observed in 77.8% of individuals, the ε4 allele in 13.2% and the ε2 allele in 9%. Our data are in agreement with the results of researchers from around the world [ 12 , 14 , 15 ] as well as from domestic researchers [ 4 , 35 ]. For example, 70.4% had the ε3/ε3 genotype, 9% had the ε3/ε4 genotype, and 6% had the ε2/ε3 genotype, according to I.B.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ε3 allele was observed in 77.8% of individuals, the ε4 allele in 13.2% and the ε2 allele in 9%. Our data are in agreement with the results of researchers from around the world [ 12 , 14 , 15 ] as well as from domestic researchers [ 4 , 35 ]. For example, 70.4% had the ε3/ε3 genotype, 9% had the ε3/ε4 genotype, and 6% had the ε2/ε3 genotype, according to I.B.…”
Section: Discussionsupporting
confidence: 92%
“…High levels of depression were observed 1.9 times more frequently in carriers of the ε4 allele than in those with no depression and 1.28 times more frequently than in those with moderate levels of depression. Our data are consistent with both the results of domestic researchers, who concluded that carrying the ε4 allele of the APOE gene is an unfavorable factor contributing to the development of depression [ 35 ], and the results of a large-scale meta-analysis conducted by W.W. Wang, et al 2019 [ 36 ]. The meta-analysis was a review of 398 sources of information on the association between the ε4 allele of the APOE gene and depression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation